Pembelajaran TIK pada Siswa Kelas X.5 di SMA Negeri 8 Maros - Muh Inal Alsyahrani; Abd Muqtadir Rapi; Nasir Nasir (Lembaga Pengembangan Kinerja Dosen, 2024)
Cultural development in Indonesia, driven by science and technology, places education as the key to achieving national goals. Focusing on the practice stage in educational technology provides practical experience at SMA Negeri 8 Maros. Informatics learning involves programming, artificial intelligence, and computer networks. Research at SMA Negeri 8 Maros involved 35 class X.5 students with a focus on Information and Communication Technology (ICT). Strengthening the Teaching Profession (P2K) from 4 September to 30 October 2023, creating innovative learning tools for the integration of office applications. Students are required to master office applications and online communication skills. The Pancasila student profile emphasizes critical thinking skills, independence and creativity. The results of implementing Informatics learning using the PBL model show a positive impact on student motivation, increasing enthusiasm, and building critical thinking skills. Students who apply PBL produce higher grades. Informatics learning classification is important for understanding computational thinking and computer systems. The application of the PBL model has a positive impact making students more creative and independent in creating projects using Microsoft Office.